Flood-Irrigated Corn Silage Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2001)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn silage production.
MF581_2001_10
Keywords: MF581; Economics; Crops; MF